2016
DOI: 10.1097/md.0000000000005061
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve sheath diameter threshold by ocular ultrasonography for detection of increased intracranial pressure in Korean adult patients with brain lesions

Abstract: Optic nerve sheath diameter (ONSD) seen on ocular US has been associated with increased intracranial pressure (IICP). However, most studies have analyzed normal range of ONSD and its optimal cut-off point for IICP in Caucasian populations. Considering ONSD differences according to ethnicity, previous results may not accurately reflect the association between IICP and ONSD in Koreans. Therefore, we conducted this study to investigate normal range of ONSD and its optimal threshold for detecting IICP in Korean pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
2
35
1
1
Order By: Relevance
“…In addition, the upper normal ONSD limit (5.2 mm) and the upper bound of the 95% CI (4.14 mm) for the mean ONSD value corroborated with the optimal cut-off value for the identification of elevated ICP suggested by previous studies where the lowest bound of ONSD values was ≥5.2 mm in patients with elevated ICP 30 36 . Although some authors insist that ONSD is influenced by ethnicity, we could not find obvious differences between Korea and other countries 13 , 14 , 16 , 35 , 37 .…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, the upper normal ONSD limit (5.2 mm) and the upper bound of the 95% CI (4.14 mm) for the mean ONSD value corroborated with the optimal cut-off value for the identification of elevated ICP suggested by previous studies where the lowest bound of ONSD values was ≥5.2 mm in patients with elevated ICP 30 36 . Although some authors insist that ONSD is influenced by ethnicity, we could not find obvious differences between Korea and other countries 13 , 14 , 16 , 35 , 37 .…”
Section: Discussioncontrasting
confidence: 96%
“…These discrepancies may depend on various factors, including the execution technique, the subject selection, the underlying pathology and ethnicity, limiting the validation of the method for a more extensive use. Our optimal cut‐off point for the detection of raised ICP was 5.6 mm, being in‐line with cited previous reports and more recent findings …”
Section: Discussionsupporting
confidence: 91%
“…Our optimal cut-off point for the detection of raised ICP was 5.6 mm, being in-line with cited previous reports and more recent findings. 30,31 This study presents some limitations like the small study population and that we presumed that ICP was normal in control subjects without performing a CSF opening pressure evalua-tion. Additionally, we are aware of the limited predictive value of abnormal CT findings in the assessment of ICP.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the East Asian population, a recent study conducted on healthy Chinese volunteers reported a mean ONSD of 5.1 mm (range, 4.7–5.4 mm) and a study performed on a Korean population found a mean ONSD of 4.9 mm (range, 4.6–5.2 mm) in the normal control group, similar to that of the healthy Chinese population, and a mean ONSD of 5.9 mm (range, 5.8–6.2 mm) in the IICP group diagnosed using brain CT scans, with a cut-off value of 5.5 mm [ 7 , 8 ]. However, these studies did not correlate ONSD with directly measured ICP.…”
Section: Discussionmentioning
confidence: 89%